Specificity of professional self-actuating of the employees of the State Penitentiary Service of Ukraine - O. M. Kokun (Law and Safety)
The specifics of professional activity of the employees of the State Penitentiary Service (SPS) of Ukraine have been revealed; and the definition of personal and professional self-actuating of the employees of SPS of Ukraine has been offered.